Recognition of Hg 2+ and Cr 3+ in physiological conditions by a rhodamine derivative and its application as a reagent for cell-imaging studies - Saha, Sukdeb; Mahato, Prasenjit; Reddy, Upendar G.; Suresh, E.; Chakrabarty, Arindam; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Inorganic Chemistry, 2012)
A new rhodamine-based receptor, derivatized with an additional fluorophore (quinoline), was synthesized for selective recognition of Hg2+ and Cr3+ in an acetonitrile/HEPES buffer medium of pH 7.3. This reagent could be used as a dual probe and allowed detection of these two ions by monitoring changes in absorption and the fluorescence spectral pattern. In both instances, the extent of the changes was significant enough to allow visual detection. More importantly, the receptor molecule could be used as an imaging reagent for detection of Hg2+ and Cr3+ uptake in live human cancer cells (MCF7) using laser confocal microscopic studies. Unlike Hg(ClO4)2 or Hg(NO3)2 salts, HgCl2 or HgI2 failed to induce any visually detectable change in color or fluorescence upon interaction with L1 under identical experimental conditions. Presumably, the higher covalent nature of HgII in HgCl2 or HgI2 accounts for its lower acidity and its inability to open up the spirolactam ring of the reagent L1. The issue has been addressed on the basis of the single-crystal X-ray structures of L1·HgX2 (X– = Cl– or I–) and results from other spectral studies.

CN? specific turn-on phosphorescent probe with probable application for enzymatic assay and as an imaging reagent - Reddy, Upendar G.; Das, Priyadip; Saha, Sukdeb; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2013)
A new “turn-on” luminescence probe for imaging the uptake of 0.2 ppm inorganic CN− in live HeLa cells as well as for probing the CN− generation through an enzymatic process in a virtual aqueous medium at appropriate pH.

Designing a thiol specific fluorescent probe for possible use as a reagent for intracellular detection and estimation in blood serum: kinetic analysis to probe the role of intramolecular hydrogen bonding - Das, Priyadip; Mandal, Amal Kumar; Reddy, Upendar G.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic & Biomolecular Chemistry, 2013)
A new and simple chemodosimetric probe L-1 is utilized for the selective detection of biothiols in the presence of other relevant amino acids under physiological conditions (pH = 7.4). This eventually led to a turn-off luminescence response due to an effective photoinduced electron transfer based signaling mechanism. A comparison of the results of the fluorescence kinetic analysis and H-1 NMR studies of the reaction between thiol and L-1 or the analogous compound L-2 revealed the role of intramolecular hydrogen bonding in activating the imine functionality towards nucleophilic addition. Such an example is not common in contemporary literature. Conventional MTT assay studies revealed that this probe (L-1) has low cytotoxicity. Results of the cell imaging studies revealed that this probe was cell membrane permeable and could detect the intracellular distribution of biothiols within living HeLa cells. Furthermore, our studies with human blood plasma demonstrated the possibility of using this reagent for the quantitative optical detection of total biothiols in biological fluid. Such an example for the detection of biothiols in real biological samples is rare in the contemporary literature. These results clearly demonstrate the possibility of using this reagent in medicinal biology and diagnostic applications.

New receptor with a FRET based fluorescence response for selective recognition of fumaric and maleic acids in aqueous medium - Reddy, Upendar G.; Lo, Rabindranath; Roy, Sovan; Banerjee, Tanmay; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2013)
Preferential binding of a new reagent to fumaric acid could be utilized for its estimation in aqueous medium and in commercial fruit juice.

Novel fluorescence probe for estimation of cysteine/histidine in human blood plasma and recognition of endogenous cysteine in live Hct116 cells - Reddy, Upendar G.; Agarwalla, Hridesh; Taye, Nandaraj; Ghorai, Suvankar; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new Cu(II)-complex is used as a ``Turn-On'' luminescence probe for specific detection of endogenous Cys in live Hct116 cells and Cys present in human blood plasma without any interference from other amino acids, especially GSH and Hcy. Difference in the mechanistic pathway for Cys and His recognition is discussed.

Specific probe for Hg2+ to delineate even H+ in pure aqueous buffer/Hct116 colon cancer cells: Hg(II)-eta(2)-arene pi-interaction and a TBET-based fluorescence response - Reddy, Upendar G.; Ramu, Vadde; Roy, Sovan; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new molecular probe that demonstrates a distinct TBET process, induced by the Hg(II)-eta(2)-arene pi-interaction, in pure aqueous medium with a large pseudo-Stokes shift of 200 nm.

Superior grafting and state-of-the-art interfacial electron transfer rates for newly designed geminal dicarboxylate bound ruthenium(II)- and osmium(II)-polypyridyl dyes on TiO2 nanosurface - Banerjee, Tanmay; Biswas, Abul Kalam; Reddy, Upendar G.; Sahu, Tuhin Subhra; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2014)
Two new Ru(II)-/Os(II)-polypyridyl based sensitizer dyes with geminal dicarboxylic acid group as the binding unit for superior grafting of the dye to TiO2 have been designed and synthesized. Steady-state photochemical studies of the two sensitizer dyes in presence of TiO2 in water confirm strong binding of the dyes to TiO2. Femtosecond transient absorption studies of these newly synthesized dyes on TiO2 nanosurface have been carried out in water and the results have been compared with those for the corresponding 4,4'-dicarboxy-2,2'-bipyridine analogues of the dyes. While the charge recombination rates are considerably slower, interestingly, the electron injection rates are very fast for multiple saturated C-C linkages present between the chromophoric core and the anchoring moiety. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This is the first report on the ultrafast transient absorption studies of dyes with geminal dicarboxylic acid binding groups, which we believe will add significantly to the present research efforts toward the development of robust and efficient dyes for use in dye solar applications.

FRET-based probe for monitoring pH changes in lipid-dense region of Hct116 cells - Reddy, Upendar G.; Anila, H. A.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Organic Letters, 2015)
A rhodamine conjugate (L) with a pseudo Stokes shift of 165 nm is used for probing changes in solution pH under physiological conditions. This reagent is found to be nontoxic, and the luminescence response could be used for imaging changes in endogenous pH induced by dexamethanose (DMT) in the endoplasmic reticulum.

New turn on Pd2+-specific fluorescence probe and its use as an imaging reagent for cellular uptake in Hct116 cells - Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new coumarin-rhodamine conjugate is used as a specific probe for Pd2+ ions and this could even delineate Pd(II) from Pd(0) or Pd(IV) in aqueous buffer medium (pH similar to 7). Laser confocal microscopic studies reveal that efficient cellular internalization of this reagent helps in imaging the cellular uptake of Pd2+ as low as 0.1 ppm in Hct 116 cells. This reagent could even be used for estimation of Pd2+ in human urine samples.

Reagent for specific recognition of cysteine in aqueous buffer and in natural milk: imaging studies, enzymatic reaction and analysis of whey protein - Anila, H. A.; Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
We report a new chemodosimetric probe (L) for specific recognition of cysteine (Cys) in aqueous buffer and in whey protein isolated from fresh cow's milk. Using this reagent we could develop a luminescence-based methodology for estimation of Cys released from a commercially available Cys-supplement drug by aminoacylase-1 in live cells.